DIDACTIC METHODS ON THE UPBRINGING OF A CHILD IN THE WORK OF ABDULLAH AVLANI “TURKISH GULISTAN YOHUD ETHICS - Gazieva Feruza Otakozievna (Journal of new century innovations, 2022)
Annotation: this article talks about the methods of upbringing mentioned in the work of the famous children adibi and the first Uzbek pedagogue Abdullah Avlani “Turkish Gulistan yohud morals”. A.It is revealed how the consequences of immaturity reflected in avlonian stories affect the decline of society.